2021
DOI: 10.3389/fimmu.2021.678355
|View full text |Cite
|
Sign up to set email alerts
|

The Alterations in and the Role of the Th17/Treg Balance in Metabolic Diseases

Abstract: Chronic inflammation plays an important role in the development of metabolic diseases. These include obesity, type 2 diabetes mellitus, and metabolic dysfunction-associated fatty liver disease. The proinflammatory environment maintained by the innate immunity, including macrophages and related cytokines, can be influenced by adaptive immunity. The function of T helper 17 (Th17) and regulatory T (Treg) cells in this process has attracted attention. The Th17/Treg balance is regulated by inflammatory cytokines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 146 publications
(172 reference statements)
1
95
0
Order By: Relevance
“…Altered Th17/Treg balance in obesity, T2D, and NAFLD * [85] ↑pro-inflammatory cytokines in DIO mice [86,87] ↑IL-17-producing γδ T cells [87,88] and ↑IFN-γ-producing Th1 and CD8 + T cells [87] in DIO mice ↓IL-22 in db/db, ob/ob, and DIO mice [89] ↓Tregs in DIO mice * [85][86][87]89,90] ↓eosinophils in DIO mice [91] Altered Th1/Th2 [92], Th1/Th17 [93,94], Th1/Treg [95] and/or Th17/Treg balance [92,94,95] in IBD * ↑Th1 responses (↑IFN-γ) in CD * [96,97] ↑Th2 responses (↑IL-4 and IL-5) in UC * [96,98] ↑Th17 (↑IL-17, IL-21, and IL-22) in IBD * [99] ↑Th1 or Th17 responses (↑IFN-γ and IL-17) in CD, and↑NK T (↑IL-13), IL-4, IL-5 in UC [98,100] ↑Th1-like Th17 (↑IFN-γ and IL-17), T17-like Treg in CD [101] ↑Th1-like Treg (↑IFN-γ) in both CD and UC [102] ↑plasticity of ILC3s (NKp44 + NKp46 + ) to ILC1s (NKp44 − NKp46 − ) and ↑plasticity of ILC2s to ILC1s in CD [103,104] ↓ILCreg in IBD [105,106] * Possible links between metabolic disorders and IBD.…”
Section: Intestinal Immune Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered Th17/Treg balance in obesity, T2D, and NAFLD * [85] ↑pro-inflammatory cytokines in DIO mice [86,87] ↑IL-17-producing γδ T cells [87,88] and ↑IFN-γ-producing Th1 and CD8 + T cells [87] in DIO mice ↓IL-22 in db/db, ob/ob, and DIO mice [89] ↓Tregs in DIO mice * [85][86][87]89,90] ↓eosinophils in DIO mice [91] Altered Th1/Th2 [92], Th1/Th17 [93,94], Th1/Treg [95] and/or Th17/Treg balance [92,94,95] in IBD * ↑Th1 responses (↑IFN-γ) in CD * [96,97] ↑Th2 responses (↑IL-4 and IL-5) in UC * [96,98] ↑Th17 (↑IL-17, IL-21, and IL-22) in IBD * [99] ↑Th1 or Th17 responses (↑IFN-γ and IL-17) in CD, and↑NK T (↑IL-13), IL-4, IL-5 in UC [98,100] ↑Th1-like Th17 (↑IFN-γ and IL-17), T17-like Treg in CD [101] ↑Th1-like Treg (↑IFN-γ) in both CD and UC [102] ↑plasticity of ILC3s (NKp44 + NKp46 + ) to ILC1s (NKp44 − NKp46 − ) and ↑plasticity of ILC2s to ILC1s in CD [103,104] ↓ILCreg in IBD [105,106] * Possible links between metabolic disorders and IBD.…”
Section: Intestinal Immune Dysfunctionmentioning
confidence: 99%
“…In addition, the balance between Th17 and Treg cells in the intestine is also closely connected with the pathogenesis of obesity and related metabolic disorders. Many studies have shown that the Th17/Treg balance is regulated by inflammatory cytokines and various metabolic factors, as well as interaction with gut microbiota, and its alteration has important roles in the development of chronic inflammatory metabolic disorders such as obesity, T2D, and NAFLD [85]. Besides, HF-induced depletion of intestinal eosinophils was also demonstrated to lead to a loss of barrier integrity in DIO mice, but the underlying mechanism needs to be clarified [91].…”
Section: Intestinal Pro-inflammatory State Induced By Metabolic Disordersmentioning
confidence: 99%
“…The differentiation of Th17 cells is regulated by multiple cytokines, including IL-4 [ 29 ]. These cells secrete interleukins, stimulating the production of pro-inflammatory molecules implicated in the pathogenesis of metabolic diseases [ 30 ]. Hence, the reduction in hepatic levels of IL-17, together with the increase in IL-4 could be involved in the anti-inflammatory profile found in the liver of leptin-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 acting on neutrophils and fibroblasts fuels local inflammation and tissue destruction by inducing production of neutrophil chemoattractants, MMPs, and ROS. In turn, recruited neutrophils produce chemokines (CCL2, CCL20) that further recruit Th17 cells [ 58 , 77 , 78 , 79 , 80 ].…”
Section: Pathogenesis Of Periodontitismentioning
confidence: 99%
“…In DM the proinflammatory environment created by macrophages and inflammatory cytokines favors differentiation of naive CD4 + T cells in proinflammatory Th17 rather than in regulatory Treg [ 80 ]. In addition, the excess of glucose and lipid can also contribute to increasing the Th17/Treg ratio through modulation of nutrient sensing intracellular pathways (mTOR, AMPK, HIF-1) that are crucial in driving differentiation of naive CD4 + T cells towards either Th17 or Treg [ 80 ]. In turn, Th17/Treg imbalance can further fuel inflammation.…”
Section: Mechanisms Linking Periodontitis and Dmmentioning
confidence: 99%